ESTIMATION OF THERMODYNAMIC PARAMETERS OF Ni-Si BASE ALLOYS USING THE SEMI-EMPIRICAL MIEDEMA MODEL - Ali Kadhim Alsaedi; Faiz Salih Abbas; Azhar S. Alaboodi; Abojassim, Ali Abid (Malaysian Journal of Science, 2022)
In this paper, we present a calculation method for evaluating the possibility of enhancing the thermal stability of nickel silicide by alloying with metals, which consists in determining the formation enthalpy (∆H) of nickel silicide using the Miedema model. Changes in formation enthalpy (∆H) were observed for nickel silicides that were alloyed with Mo, Pt, Pd, W, and Zr. The MAAT (Materials Analysis Applying Thermodynamics) software was used to calculate and plot the formation enthalpy of binary and ternary systems. Based on our calculations, we found that in binary systems, the optimum values to expand the formation enthalpy were 51.28 and 49.57 kJ/mol for nickel silicide alloys. For the ternary system, the results showed that adding Zr could increase monosilicide phase stability.